Os exus em casa de catiço : etnografia, representações, magia - Queiroz, Marcos Alexandre de Souza (2008)
This dissertation is the result of an ethnographic journey undertaken in three spiritual centers of Umbanda , located in different districts of Natal/RN. The aim of the study was to understand how the representations of exus (spirit category) are established in the studied religious environment. In order to study this, mythical narratives of songs and of people were analyzed. In addition, the incorporated spirit entities, loaded with codes and values, were possible to be read and understood. The present work was developed according to a theoretical and methodological approach that interprets culture as a constant construction process, with representations and significations. The empirical research focuses on the ethnographic observations and the narratives; providing the experimentation of the models of discursive dialogues and polyphony. It was observed that the studied empirical field is marked by the cult of the Jurema which influences the mythical construction of exus . Therefore, this study enabled a reflection on the meeting of notions of two distinct worlds ( Umbanda and Jurema ). This reflection is crucial to the understanding of the position that exus occupy in the local umbandista system